Usages prescrits et figure de l’utilisateur modèle dans le design du web-documentaire B4, fenêtres sur tour - Samuel Gantier (Communication)
This article considers how the various professionals involved in designing an interactive web documentary anticipate and negotiate the uses of the eventual “acting spectator” (spectateur-actant). The author recorded his observations during his participation in six months of design work on B4, fenêtres sur tour, an interactive web documentary coproduced by France Télévision’s Nouvelles Écritures. His analytic framework highlights all the sociotechnical and semio-pragmatic controversies that shaped the making of the documentary. A three-dimensional figure of the “model user” is then formalized. The exogenous, interactional, and capability dimensions of this model user ultimately provided a methodological lesson in the designing of such an emergent, non-stabilized format.